The Social Services : The immediate problem and the way forward (London : The Socialist Medical Assocation)
1944 1944 1940s 34 pages highly skilled workers, such as advice bureaux. Professional workers, through their organisations, must play an important part in raising the standard of work in such services, but their quality will depend almost as much on the attitude adopted by their clients, or potential clients. There is still a great deal to be done in educating the public, and especially members of Local Authorities, on the conduct of social services, and this seems to be an appropriate field of work for the voluntary organisations. 11. Voluntary and professional work Social services on the scale which we envisage cannot be run entirely by the small number of trained professional workers at present available, nor is it desirable that they should be run "for" the people by a small professional class. Their success will depend on the extent to which they are run "by" the people. The voluntary worker, far from disappearing, will have an important role to play. But the voluntary workers of the future will not be drawn, like most of those of the past, from a leisured class, for this class is disappearing and few would wish to revive it. But there is a great reserve of potential volunteers in the thousands of devoted workers who have built up the Labour Movement. Many of these are already doing a great deal to build and run social services. Co-operative societies have used their resources to 23 15X/2/464/1